2012
DOI: 10.1073/pnas.1120791109
|View full text |Cite
|
Sign up to set email alerts
|

Nonimmunoglobulin target loci of activation-induced cytidine deaminase (AID) share unique features with immunoglobulin genes

Abstract: Activation-induced cytidine deaminase (AID) is required for both somatic hypermutation and class-switch recombination in activated B cells. AID is also known to target nonimmunoglobulin genes and introduce mutations or chromosomal translocations, eventually causing tumors. To identify as-yet-unknown AID targets, we screened early AID-induced DNA breaks by using two independent genome-wide approaches. Along with known AID targets, this screen identified a set of unique genes (SNHG3, MALAT1, BCL7A, and CUX1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 61 publications
3
71
1
1
Order By: Relevance
“…In CSR, FACT contributes to the DNA break by promoting the trimethylation of H3K4 (16). Regarding SHM, we reported that H3K4me3 is enriched in SHM target regions (5). However, as H3K4me3 is a common modification on active chromatin, the targeting mechanism for CSR and SHM cannot be fully explained by the level of H3K4me3.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…In CSR, FACT contributes to the DNA break by promoting the trimethylation of H3K4 (16). Regarding SHM, we reported that H3K4me3 is enriched in SHM target regions (5). However, as H3K4me3 is a common modification on active chromatin, the targeting mechanism for CSR and SHM cannot be fully explained by the level of H3K4me3.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, we proposed that the H3K4me3 chromatin modification is a marker for CSR. We later showed that H3K4me3 also accumulates at SHM-targeted genomic regions, indicating that this histone modification is important for the induction of both CSR and SHM (5).…”
Section: Aid | Ssrp1mentioning
confidence: 83%
See 3 more Smart Citations